Characterisation and molecular studies of plasmids from Nigerian staphylococci - Udo, Edet Ekpenyong (Curtin University, 1991)
Fifty three Staphylococcus aureus isolates were obtained from three centres, two hospitals and a private pathology laboratory, and studied for susceptibility to bacteriophages, resistance to antimicrobial agents and plasmid contents.Results of bacteriophage typing revealed that they belonged to a variety of phage types. Eighteen were untypable by any of the International Set of Phages, 16 belonged to phage group 111, nine to group I, four to group 11, two to group IV and two to the miscellaneous group.The isolates were resistant to one or more of methicillin (Mc), benzyl penicillin (Pc), gentamicin (Gm) , kanamycin (Km) , neomycin (Nm) , streptomycin (Sm) , trimethoprim (Tp), sulphonamides (Su), tetracycline (Tc), minocycline (Mn), chloramphenicol (Cm), novobiocin (Nb) and fusidic acid (Fa). Resistance to Pc was due to the production of beta-lactamase (Bla). No resistance to vancomycin, spectinomycin and erythromycin was detected. Resistance was also found to heavy metals such as cadmium (Cd), mercury (Hg), phenyl mercuric acetate (Pma), arsenate (Asa) and to the nucleic-acid binding compounds propamidine isethionate (Pi) and ethidium bromide (Eb).All but one of the isolates harboured plasmids. The number of plasmids the isolates carried varied from one to six and their sizes ranged from < 1.0 kb to c.48 kb.Location of the resistance determinants was ascertained by curing and transfer experiments. Loss of resistance was tested after growth at 43.5°C and transfer of resistance determinants was attempted by transduction, mixed-culture transfer and conjugation. The results revealed that resistance to Mc, Gm, Tp, Mn and Fa was chromosomal in all the resistant isolates and in some isolates Bla and resistance to Sm and Cd were chromosomal as well as plasmid encoded. In the majority of cases Bla and resistance to Km, Nm, Sm, Tc, Cin, Cd, Hg, Asa, Pma, Pi and Eb was encoded by plasmids.Conjugation experiments led to the isolation of three unique conjugative plasmids which have not been found to confer resistance to antimicrobials or to produce haemolysins or diffusible pigment (Dip). The three plasmids, pWBG620, pWBG637 and pWBG661, were indistinguishable by restriction endonuclease analysis and DNA-DNA hybridisation. However pWBG620, unlike pWBG637 and pWBG661, was not detected in the cytoplasm of its host and was only detected in transconjugants after it mobilised a non-conjugative Sm-resistance (SmR) plasmid. Further analysis indicated that it is integrated into the chromosome of its host, excises during conjugation and mobilises the SmR plasmid.These plasmids were studied further using pWBG637 as a representative. It was compared with representatives of the two groups of conjugative plasmids which have been reported in the staphylococci. These are the plasmids which encode resistance to Gm, Km and Nm and those which code for the production of diffusible pigment. The three types of conjugative plasmids were compared by restriction endonuclease analysis and DNA- DNA hybridisation and were found to be different. A preliminary restriction map of pWBG637 has also been constructed.However since pWBG637 has no resistance phenotype direct selection for it was not possible in transfer experiments and for incompatibility (Inc.). To study it further it was necessary to construct resistant derivatives which could be selected for in transfer experiments. This was achieved by labelling pWBG637 with resistance transposons to generate two conjugative plasmids, pWBG636 carrying an insert of Tn3851 (Gm- resistance) and pWBG642 carrying an insert of Tn551 (hn- resistance). It was found that transposon labelling had not changed the incompatibility of pWBG637 and therefore pWBG636 and pWBG642 were used in further experiments in place of pWBG637. Inc. tests with the pWBG637 derivatives revealed that the pWBG637 type of plasmid is not only different from the other two types of conjugative plasmids but is different from any of the described staphylococcal Inc. groups and therefore the pWBG637 type of plasmids represent a new Inc. group 15. The pWBG637 type of plasmids were studied further using plasmids pWBG636 and pWBG642. They were able to transfer conjugatively to a capsulated S.aureus strain either by the polyethylene glycol method or on filter membranes. They also transferred by conjugation to S. epidermidis and Streptococcus faecalis and were able to transfer back from these strains to S.aureus indicating that they also replicate in these hosts. Consequently they have been used to mobilise non-conjugative plasmids from S.epidermidis and non phage typable S.aureus. Both plasmids failed to transfer conjugatively to Bacillus subtilis and Escherichia coli.pWBG637 transferred non-conjugative plasmids by mobilising them in a manner similar to mobilisation (donation) in E.coli or by recombining with them to form new resistance plasmids. In one case, pWBG628 which encodes Bla and resistance to Cd, Km, Nm and Sm and has no homology with pWBG637 recombined with it during conjugation to produce three new conjugative plasmids pWBG629, pWBG630 and pWBG631 carrying resistance determinants from pWBG628. One of these plasmids, pWBG629, was found to be pWBG637 which had acquired a 4.5 kb element encoding resistance to Km, Nm and Sm. This element was shown to be transposable in both rec+ and rec- backgrounds and has been designated Tn3854. It expressed Sm resistance in E.coli and differs on this account from the Gram-negative transposon Tn5 which expresses resistance to Km, Nm and Sm in non-enteric bacteria but only resistance to Km and Nm in E. coli.Where possible the non-conjugative plasmids encoding resistance to antimicrobial agents were compared with phenotypically similar plasmids isolated from other parts of the world. It was found that the Tc and Sm resistance plasmids were closely related to other plasmids with the same phenotype whereas the Cm resistance plasmids were different.Although the majority of the Bla plasmids belonged to Inc. group 1 they demonstrated significant restriction enzyme fragment length polymorphism when compared with other Bla plasmids.This study has provided the first data on the genetics of antimicrobial resistance in Nigerian S.aureus. Although many of the plasmids studied were found to be similar to those previously described the isolates also contained some unique and previously undescribed plasmids.